Pengaruh Kompensasi, Komitmen Organisasional, dan Kompetensi terhadap Kinerja Karyawan pada Perusahaan Do'a Property di Semarang - Lina Aliyah Tusifa; Tristiana Rijanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of damage, organizational commitment and competence on the performance of employees of the Do'a Property company in Semarang. The type of data used is primary data, namely data obtained directly from original sources in the form of questionnaires. The population of this research is employees of the Do'a Property Semarang company totaling 70 people. Sampling was carried out using a purposive sampling technique, namely a sampling technique using the criteria of being permanent employees, working period of at least 3 years and having a minimum of high school/vocational school education, so that a sample of 60 respondents was obtained. The data collected was analyzed using factor analysis to test the validity of the question items, test reliability using Cronbach Alpha, and test hypotheses using multiple linear regression. The research results show that the compensation variable has no effect on employee performance, the organizational commitment variable has a positive and significant effect on employee performance, and the competency variable has a positive and significant effect on employee performance.